1985
DOI: 10.1111/j.1365-2222.1985.tb02295.x
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial allergy in cystic fibrosis

Abstract: Summary Thirty‐one patients with cystic fibrosis (CF) were thoroughly evaluated for allergy. This included a clinical history, skin tests with twenty‐three allergens and bronchial provocation with inhaled allergens and histamine. The bronchial response was measured by whole body plethysmography. Of the patients studied, 40% 0 showed a bronchoconstrictor response to inhaled allergens, despite the fact that none had reported asthma in their clinical history. Strong skin test reactions (3+ and 4+) and weak reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Overall, 61% of patients showed a significant reaction as a result of BAP. These data are in line with a study that demonstrated that even among weak skin reactions to A fumigatus , 43% are associated with a positive reaction in BAP . Furthermore, the hypothesis that sensitization translates to clinical susceptibility like an asthmatic reaction was demonstrated by a significant correlation between sIgE sensitization (quantification) to cumulative BAP dose sensitivity.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Overall, 61% of patients showed a significant reaction as a result of BAP. These data are in line with a study that demonstrated that even among weak skin reactions to A fumigatus , 43% are associated with a positive reaction in BAP . Furthermore, the hypothesis that sensitization translates to clinical susceptibility like an asthmatic reaction was demonstrated by a significant correlation between sIgE sensitization (quantification) to cumulative BAP dose sensitivity.…”
Section: Discussionsupporting
confidence: 82%
“…These data are in line with a study that demonstrated that even among weak skin reactions to A fumigatus, 43% are associated with a positive reaction in BAP. 33 Furthermore, the hypothesis that sensitization translates to clinical susceptibility like an asthmatic reaction was demonstrated by a significant correlation between sIgE sensitization (quantification) to cumulative BAP dose sensitivity. In addition, eNO significantly increased after 24 hours, and patients with an LAR had significantly higher eNO levels compared to patients with a negative BAP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to exacerbated pulmonary inflammation, CF patients manifest airway obstruction and wheezing [20] and near 40-50% of these patients have airway constriction. This led us to explore the mediators involved in the induction of airway constriction in CFTR -/- mice.…”
Section: Discussionmentioning
confidence: 99%
“…All other aminoglycosides, but not the commercially available form of amikacin in France (Amiklin1), contain sulphites that may be responsible for severe allergic side effects [14]. This is particularly important in CF patients who are known to have frequent bronchial hyperreactivity [15] and are at risk of bronchial allergy [16], and this is why the present study was conducted with amikacin. In the present study, tolerance of inhalation was good for all patients and pulmonary function tests were unchanged after nebulization.…”
Section: Discussionmentioning
confidence: 99%